Penggunaan obat off-label pada pasien anak di salah satu rumah sakit daerah Provinsi Nusa Tenggara Barat tahun 2017 - Ria Hapsari; Siti Rahmatul Aini; Candra Dwipayana Hamdin (Sasambo Journal of Pharmacy, 2023)
Due to insufficient pharmacokinetic-pharmacodynamic data, off-label medication usage in children is commonly observed. It might result in Drug Related Problems (DRPs) that could lead to morbidity in youngsters. In one of West Nusa Tenggara Province's public hospitals, this study sought to gain a general understanding of pediatric patients between the ages of 4 and 14 who were using off-label medications. Retrospective descriptive methodology is used in this investigation. For each of the following categories: age, indication, contraindication, dosage, and method of administration, the percentage of off-label drug use was calculatedbased on medical records and literature reviews. Out of 302 medications prescribed to outpatients, 14 (4.63%) and 5 (1.65%) were off-label for the patient's age, and indication categories were determined.Regarding inpatients, out of 369 medicines, the categories for age, indication, and dose, respectively, indicated 7.85% (29), 1.08% (4), and 2.43% (9) off-labels. Both pediatric inpatient and outpatient patients were found to be using drugs off-label. To ascertain the impact of off-label pharmacological advantages on the efficacy of drug therapy, more research is required.